Testing Interconnected Systems with Behavior Mining - Schieweck, Alexander; Margaria, Tiziana (Electronic Communications of the EASST, 2021)
Modern software applications rely not only on a complex stack of technologies, but are more and more dependent on and connected to third party interfaces, Internet of Things devices and Industry 4.0 machines. One approach to tackle this complexity is Model Driven Design with custom interactions. But it is then still necessary to test the whole system to ensure that all parts work together as intended. This paper looks at the possibility of using Active Automata Learning as a systematic way to test interconnected systems.